2023
DOI: 10.3390/healthcare11111652
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Micronutrients in Human Papillomavirus Infection, Cervical Dysplasia, and Neoplasm

Abstract: There is evidence that diet and nutrition are modifiable risk factors for several cancers. In recent years, attention paid to micronutrients in gynecology has increased, especially regarding Human papillomavirus (HPV) infection. We performed a review of the literature up until December 2022, aiming to clarify the effects of micronutrients, minerals, and vitamins on the history of HPV infection and the development of cervical cancer. We included studies having as their primary objective the evaluation of dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 108 publications
(209 reference statements)
0
2
0
Order By: Relevance
“…The regression rates were significantly lower in non-pregnant women [ 5 7 ]. Diet and nutrition are modifiable risk factors for several cancers and the regression rate of CIN is demonstrated to be influenced by several variables, in particular calcium; zinc; iron; selenium; carotenoids; and vitamins A, B12, C, D, E, and K. Different oligo-elements and micronutrients have demonstrated a potential protective role against cervical cancer by intervening in different stages of the natural history of CIN [ 8 ].…”
Section: Natural Course Of Cervical Intraepithelial Neoplasia In Preg...mentioning
confidence: 99%
“…The regression rates were significantly lower in non-pregnant women [ 5 7 ]. Diet and nutrition are modifiable risk factors for several cancers and the regression rate of CIN is demonstrated to be influenced by several variables, in particular calcium; zinc; iron; selenium; carotenoids; and vitamins A, B12, C, D, E, and K. Different oligo-elements and micronutrients have demonstrated a potential protective role against cervical cancer by intervening in different stages of the natural history of CIN [ 8 ].…”
Section: Natural Course Of Cervical Intraepithelial Neoplasia In Preg...mentioning
confidence: 99%
“…Strategies for preventing the development of gynecologic cancers include regular gynecologic check-ups, human papillomavirus (HPV) vaccination or physical activity and a healthy diet [2,3]. In the past two decades, many publications have focused attention on the role of micronutrients in the prevention of gynecologic malignancies [4][5][6]. Extensive meta-analyses have shown that daily supplementation with vitamin A and D3 can reduce the incidence of ovarian cancer [7][8][9], as well as mortality from malignant cancer by up to 12% [9].…”
Section: Introductionmentioning
confidence: 99%